Perfet target - Solomon, Lee; Tabrizi, Alexander; Lettich, Sheldon (La Crosse, Wis. Platinum Disc Corp., 1998)
A quiet life in a sleepy Latin America country comes to an explosive end when an American expatriate becomes the PERFECT TARGET in a deadly political coup. David Bensen blasts on screen with pure power as an ex-CIA agent forced back to work as a mercenary to escape imprisonment on false charges. When his ex-boss, Colonel Shackwell assigns him to the reigning president of Santa Brava, he never expects to be the fall guy for his murder. Now, with an army of Shackwell's henchmen hunting him down, he's on the run with local police captain, David Ramirez, also falsely accused of the assassination. Their only hope is to expose the true terrorists behind the plot, and exonerate themselves. It will take every bit of their cunning military strategies and brute force to bring down the treacherous traitors. In a blaze of guns, glory and poetic justice, the final move is played in a game of winner take all.
A Sheldon Lettich film.
Original screenplay by Peter Bronsnan, Michael Lanahan and George Saunders.
Music by David Michael Frank ; Edited by Donn Aron ; Director of photography, Jesus "Chuy" Chavez ; Executive producer, Christian Halsey Solomon.
Daniel Bernhardt, Robert Englund, Brian Thompson Jim Pirri, Dara Tom Anovich, Julieta Rosen, Mario Ivan Martinez and Robert Engluno.
DVD ; Dolby digital.
In English.
Keywords: Adventure films; Action; Thriller